Aparigraha - is it good for organisations?. (9th May 2019) - Bali, Aditya; Kachwala, Tohid; Sivaramakrishnan, Sreeram
Management theories have traditionally been based on concepts borrowed from western schools of philosophy with minimal influence of Indian philosophical thought. But with India emerging as an economic powerhouse post liberalisation, the age old philosophical traditions and concepts have received renewed attention from scholars for useful insights relevant to businesses. One such construct is 'Aparigraha' interpreted as non-possessiveness, non-greediness, generosity and non-envy. The importance of the practice of Aparigraha for present day businesses has been studied but sparingly. Literature pertaining to Aparigraha also lacks empirical demonstration of the tangible benefits accruing to organisations. The paper aims to bridge this gap by suggesting a methodological tool (use of experimental games) for testing the impact of practising Aparigraha on group performance in organisations. The study uses a variant of the multiplayer dictator game and concludes that a stronger belief in Aparigraha and practice of Aparigraha has a positive impact on group performance.